2023
DOI: 10.3390/molecules28052251
|View full text |Cite
|
Sign up to set email alerts
|

Ln(III) Complexes Embedded in Biocompatible PLGA Nanoparticles as Potential Vis-to-NIR Optical Probes

Abstract: In this contribution, we present the spectroscopic study of two NIR emitting hydrophobic heteroleptic (R,R)-YbL1(tta) and (R,R)-NdL1(tta) complexes (with tta = 2-thenoyltrifluoroacetonate and L1 = N,N′-bis(2-(8-hydroxyquinolinate)methylidene)-1,2-(R,R or S,S)-cyclohexanediamine), both in methanol solution and embedded in water dispersible and biocompatible poly lactic-co-glycolic acid (PLGA) nanoparticles. Thanks to their absorption properties in a wide range of wavelengths extending from the UV up to the blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recently, some of us demonstrated that the Yb(III) luminescence can be efficiently sensitized upon excitation of a conjugated ligand system in different spectral regions: from UV to Vis. 19,20 In order to efficiently sensitize the Ln(III) luminescence at NIR wavelengths, one possible strategy is the design of ligands including a two-photon absorbing chromophoric antenna capable of transferring the excitation energy to the Ln(III) ion. Two-photon (2P) excitation is a nonlinear optical phenomenon which takes place when an excited state of a chromophore can be populated by the concomitant absorption of two photons, whose wavelength is twice that of a Luminescent Materials Laboratory, DB, Universita `di Verona, and INSTM, UdR Verona, Strada Le Grazie 15, 37134 Verona, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us demonstrated that the Yb(III) luminescence can be efficiently sensitized upon excitation of a conjugated ligand system in different spectral regions: from UV to Vis. 19,20 In order to efficiently sensitize the Ln(III) luminescence at NIR wavelengths, one possible strategy is the design of ligands including a two-photon absorbing chromophoric antenna capable of transferring the excitation energy to the Ln(III) ion. Two-photon (2P) excitation is a nonlinear optical phenomenon which takes place when an excited state of a chromophore can be populated by the concomitant absorption of two photons, whose wavelength is twice that of a Luminescent Materials Laboratory, DB, Universita `di Verona, and INSTM, UdR Verona, Strada Le Grazie 15, 37134 Verona, Italy.…”
Section: Introductionmentioning
confidence: 99%